13(4x+4)=3(5x+6)

Simple and best practice solution for 13(4x+4)=3(5x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(4x+4)=3(5x+6) equation:


13(4x+4)=3(5x+6)

We simplify the equation to the form, which is simple to understand
13(4x+4)=3(5x+6)

Reorder the terms in parentheses
+(+52x+52)=3*(5x+6)

Remove unnecessary parentheses
+52x+52=+3+*(+5x+6+)

Reorder the terms in parentheses
+52x+52=+(+15x+18)

Remove unnecessary parentheses
+52x+52=+15x+18

We move all terms containing x to the left and all other terms to the right.
+52x-15x=+18-52

We simplify left and right side of the equation.
+37x=-34

We divide both sides of the equation by 37 to get x.
x=-0.91891891891892

See similar equations:

| 5x=23+y | | 100(29)=10(29) | | 2xsquared-x=3 | | Y/9-6=-14 | | 5x+9=9+2x | | 8x-11/7=-5 | | z/15-6=14 | | 3x-12=-4x+32 | | v=(p*q)-((p*q)/100*5)-p | | -2=6/8 | | 3(16-4y)4y=8 | | 8-9s+s^2= | | 1015=2x+5 | | 4-3d=8 | | -9x-6=-3(3x+2) | | d=2m+3m | | 4x+5x(-5)=21 | | 3(2n-5)=-7-2 | | -2p-5(6-2p)=5(p-2)-26 | | 3/4(a-5)=9 | | 367=4x+5 | | -500t+-4500+5750t=375t | | y=5+64 | | -16=-4/5z | | 94=-17x | | 2+2m=3(2m+2) | | 3x+x-23=9 | | 4x+3=53-6x | | 3(x-2)(x-2)=18 | | s/4=13 | | 2b-4=2b | | 15x^3-24x^2+35x-56= |

Equations solver categories